PERLINDUNGAN HUKUM TERHADAP PEKERJA/BURUH PEREMPUAN YANG BEKERJA PADA MALAM HARIDI KOTA JAYAPURA - Ismail Maswatu (INTELIGENSIA MEDIA, 2023)
This research was conducted to find out, analyze and explain the implementation of legal protection for female workers/laborers who work at night in Jayapura City and to find out, analyze and explain the factors that influence the implementation of legal protection for female workers/laborers who work at night in Jayapura city. The research method used is a normative and empirical juridical approach. These two approaches are used together because in conducting this research what is examined is not only the statutory provisions in the field of legal protection for women workers/laborers who work at night but also concerns the application of provisions in society, especially the rights of women workers/laborers. who work at night. The research results show that the implementation of legal protection for women workers/laborers who work at night such as wage protection, health insurance, leave, holiday allowances, working hour protection, security and safety guarantees at Bar New Karisma and Billiard Score 88 has not been fully implemented. the rights of women workers/labourers who work at night. Furthermore, there are several factors that influence the implementation of legal protection for women who work at night, including that the legal substance nationally is adequate but is not supported by the Jayapura City Regional Regulation concerning Guarantees for women workers/labor working at night, besides that the legal culture of the community still views that women who work in the billiard business at night carry a negative stigma for these workers/laborers and supervision from the Jayapura City Manpower Office which is still minimal has not been supported by adequate human resources and infrastructure.